Photocatalytic degradation of fluoxetine mediated by CuO/CuWO4 nanostructures - Becerra, Laura Cristina Isabel Fonseca; Malafatti, João Otávio Donizette; Paris, Elaine Cristina; Joya, Miryam Rincón; Moreira, Ailton Jose [UNESP]; Reis, Roberta Yonara Nascimento; Lima, Juliana B. [UNESP]; Vargas, Carlos Arturo Parra; Páez, Angela Mercedes Raba (Elsevier, 2025)
Background Photocatalytic activity of the CuO and CuWO4, and heterostructured based in these has been thoroughly investigated however, the Fluoxetine (FLX) degradation has not been widely explored for CuO/CuWO4 with the novel and economical synthesis method proposed in this work. Methods Four materials were produced by the co-precipitation method CuO, 100Cu/2W, 100Cu/6W, and CuWO4; 100Cu/2W and 100Cu/6W corresponding to the CuO/CuWO4 heterostructure according morphological and optical results. Significant Findings Degradation profile of FLX of 100Cu/6W and CuWO4 samples showed the lowest removal over time, while the CuO and 100Cu/2W samples showed the best performances up to 30 min under UV-C light. For the 100Cu/2W sample (CuO/CuWO4 heterostructure), the kinetic constant value was 82.3×10−2 min−1, which confirms its superiority for FLX degradation. CuWO4 (Eg = 2.70 eV) can retain the lower energy photons and after new photon absorption, transfer the e− to CuO (Eg = 3.71 eV). Furthermore, the characterization results show that the 100Cu/2W heterostructure has Eg, SBET , and particle size values intermediate between CuO and CuWO4, contributing to its better performance. Additionally, for all the materials TFMP, PPMA, and TP formation was confirmed in the first minutes of degradation. These new compounds can interact with the photocatalyst and block photocatalytic sites however, the performance of 100Cu/2W was maintained throughout the degradation time, confirming its photoactivity even in a more complex mixture containing FLX and its transformation products. The recyclability of 100Cu/2W for FLX degradation at 30 min was investigated; FLX removal increases to over 95% and is maintained until the last degradation cycle, confirming the potential of CuO/CuWO4 for application in water treatment processes. Additionally, mass spectrometry analyses were carried out for the sample subjected to photocatalytic degradation in 30 min in the presence of 100Cu/2W. There, six transformation products (TP) were identified in the sample, confirming that the degradation mechanisms of FLX involve different routes.